Lawful and unlawful foods in Islamic law focus on Islamic medical and ethical aspects - Deuraseh, Nurdeng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
In this paper, attempts will be made to study and understand the lawful and unlawful foods in the light of Islamic Medical law focus on ethical aspect that has been practiced during Islamic civilization. We will realize that lawful and unlawful foods are not, as some imagine, mere pretense, but rather constitute the divine command which protects against many diseases. In order to present such a law, the jurists of Islam needed great acuteness and power of reflection to make them understand the matters relating to lawful and unlawful foods in Islam. To attempt to follow these jurists, in their treatment, of the different school of thoughts (madhahib) would take us far beyond the limits of this research. Thus, we will rather confine ourselves to those laws which are clearly stated in the Qur'an and tradition (hadith), as well as a few of the most important issues dealt with in the different school of thoughts (madhahib).